Subliminal Brand Messages on Apple’s Data Privacy Campaign in Peirce’s Semiotics - Lazuardi, Muhammad Azhar; La Mani; Oktaviana, Cantika Nur; Darmayanti, Ni Putu Sari; Rahyadi, Irmawan (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
This research investigates the impact of hidden messages in soft-sell advertisements on consumers' perception, trust, and intention to behave towards brands, and focuses on the implications of data security and reliability. This study, a descriptive qualitative methodology combined with Charles Sanders Peirce’s semiotic analysis framework, delves into visual elements, storytelling, and advertising contexts showcased in Apple’s ad as focal points that illuminate pressing data security challenges today. The research addresses the gaps identified in prior investigations regarding the presence of subliminal cues in advertisements, illustrating that emotional engagement and subtle persuasion can bolster brand presence and distinction within the technology sector. The outcomes effectively portray its product ecosystem as a reliable data security option, underlining the significance of safeguarding personal data. Furthermore, Apple adeptly illustrates its comprehension of product placement as a strategy rooted in subliminal messaging for marketing purposes. Implies that businesses can enhance consumer trust through narrative branding and the incorporation of semiotic elements to communicate brand messages discreetly, such as assurances of data protection. Moreover, embedding products within a narrative framework has proven beneficial for boosting brand recall, emotional connection, and customer loyalty are key elements for sustaining enduring relationships with consumers who increasingly prioritize privacy. Abstrak - Penelitian ini bertujuan untuk menganalisis bagaimana pesan subliminal dalam iklan soft-selling dapat mempengaruhi persepsi, kepercayaan, dan intensi perilaku konsumen terhadap merek, khususnya terkait proposisi nilai keamanan dan keandalan data. Dengan pendekatan analisis descriptive qualitative technique dan semiotika Charles Sanders Peirce, penelitian ini mengkaji simbol visual, narasi, dan situasi periklanan dalam iklan. Apple sebagai objek kajian yang menyoroti isu keamanan data yang relevan saat ini. Penelitian ini mengisi celah studi sebelumnya terkait keberadaan sinyal subliminal dalam iklan, serta menunjukkan bagaimana resonansi emosional dan persuasi tidak langsung dapat memperkuat positioning dan diferensiasi merek dalam pasar teknologi. Hasil penelitian Apple secara efektif menunjukkan ekosistem produknya sebagai solusi keamanan data yang dapat dipercaya, menyoroti pentingnya menjaga privasi data. Apple juga berhasil menunjukkan pemahaman tentang penempatan produk sebagai pendekatan pemasaran berbasis pesan bawah sadar. Implikasi dari studi ini menunjukkan bahwa perusahaan dapat membangun kepercayaan konsumen melalui branding naratif dan penggunaan elemen semiotik untuk menyampaikan pesan merek secara halus, seperti jaminan privasi data. Selain itu, penempatan produk dalam alur cerita terbukti efektif meningkatkan daya ingat merek, keterlibatan emosional, dan loyalitas pelanggan, faktor penting dalam menjaga hubungan jangka panjang dengan konsumen.